2013
DOI: 10.1161/circulationaha.113.001971
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase G Positively Regulates Proteasome-Mediated Degradation of Misfolded Proteins

Abstract: Background Proteasome functional insufficiency is implicated in a large subset of cardiovascular diseases and may play an important role in their pathogenesis. The regulation of proteasome function is poorly understood, hindering the development of effective strategies to improve proteasome function. Methods and Results Protein kinase G (PKG) was manipulated genetically and pharmacologically in cultured cardiomyocytes. Activation of PKG increased proteasome peptidase activities, facilitated proteasome-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 42 publications
9
157
0
Order By: Relevance
“…Augmentation of PQC might, there fore, have beneficial effects in these forms of cardio myopathies. Indeed, experimental studies have already revealed that induction of proteasomal or autophagic degradation delays the onset of cardiomyopathy in mice with the Cryab R120G mutation [100][101][102] .…”
Section: Derailment Owing To Genetic Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Augmentation of PQC might, there fore, have beneficial effects in these forms of cardio myopathies. Indeed, experimental studies have already revealed that induction of proteasomal or autophagic degradation delays the onset of cardiomyopathy in mice with the Cryab R120G mutation [100][101][102] .…”
Section: Derailment Owing To Genetic Mutationsmentioning
confidence: 99%
“…Prevention of cardiac remodelling by activ ation of cGMP dependent protein kinase by sildenafil treatment in aortic banded mice 186 was subsequently demonstrated to be mediated by augmentation of the UPS in the desmin related cardiomyopathy of Cryab R120G mice 101 . Conversely, proteasome inhibition was reported to prevent and regress ventricular hypertrophy during or after chronic administration of isoprenaline in mice 187 .…”
Section: Pharmacological Modulation Of Pqcmentioning
confidence: 99%
“…In a model of desmin-related cardiomyopathy, PA28a overexpression enhances lifespan and reduces hypertrophy, abundance of mutated CryAB aggregates, as well as ubiquitinated proteins (132). Similarly, decreased GFP/CL1 abundance after PKG activation via sildenafil is associated with reduced hypertrophy, less aggregation of mutated CryAB, and preserved cardiac function in the same DRC model (173). To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars (91).…”
Section: Figmentioning
confidence: 88%
“…Additional kinases affecting proteasome activities in the heart are PKG and PKN (Fig. 4) (173,197). In contrast to the stimulating effect of protein phosphorylation on proteasome activities, oxidative modification of proteasome subunits, for example, by 4-hydroxy-2-nonenal (a byproduct of lipid peroxidation), seems to be associated with…”
Section: Impact Of Post-translational Modifications On Proteasome Actmentioning
confidence: 99%
“…The process of protein degradation by the 20S proteasome is dependent on ATP hydrolysis and appears to couple translocation, deubiquitination, and protease activity. 12 In this issue of Circulation, Ranek et al 13 build on earlier findings by this group that enhancement of proteasomal activities can protect the heart in the CryAB R120G model of desminrelated cardiomyopathy. In earlier work, these investigators used cardiomyocyte-specific overexpression of the proteasome subunit 28a (PA28a) to stimulate proteasomal activity.…”
Section: Article See P 365mentioning
confidence: 99%